Relazioni tra il lessico medico e lessico di altri livelli della lingua in rapporto all’italiano contemporaneo – alcuni casi interessanti - Szpingier, Beata Katarzyna (Wydawnictwo Naukowe UAM, 2013)
The present analysis consists of several insights into the nature and the tendencies of mutual lexical dependencies between medical language (medical terminology) and other subsystems of Italian, both common and specialist. It summarizes remarks made by numerous scholars, scattered in various compilations devoted to 'usi specialistici della lingua' (language for specfic purposes). Three kinds of relationship are brought under discussion: first, between general lexicon and medical terminology; second, between medicine conceived of as a branch and other specialized domains; third, between various scientific domains and medicine. The scope of research is by no means restricted to specialized texts. By contrast, the extent to which various inner languages are interlinked is corroborated by examples drawn from press releases encompassing various topics (news, politics, health). Detailed observations are illustrated with such Italian terms as: arteria, patologia, trauma, plasma, emorragia, polpa, tromba, and so on. It should be emphasized that mutual interference owes its existence to the upsurge of modern information technologies, as well as to an increasing access to information.
Relations between the medical lexicon and lexicon of other levels of language in relation to contemporary Italian – some interesting cases
Keywords: medical terminology; subsystem of Italian; general lexicon; relationship between specialized domains